Diagnostic Accuracy of CT-Scan Chest in Distinguishing Ground-Glass Opacities from Covid-19 Causes and Other Causes of Ground-Glass Opacities - Nadia Khattak, Najm us Samawat, Hafeez ur Rehman, Muhammad Nauman Akram, Jawad Ali Memon, Abid Rafiq Chaudhry, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Evaluation of the effectiveness of diagnostic computed tomography of the chest in differentiating between coronavirus 2019 (COVID-19) ground glass opacities and other reasons of ground glass opacities (GGO) not related to COVID-19. Place and Duration: In the department of Radiology, Miangul Abdul Haq Jahenzeb Kidney Hospital Swat for six-months duration from March 2021 to August 2021. Methods: 90 total covid-19 confirmed patients by RT-PCR having GGO (53 males and 37 females, with 47.20 ± 15.10 years mean age) and 110 patients (63 males and 47 males) who were confirmed GGO on chest CT but not due to Covid-19 were selected for the study. The experienced radiologists studied all chest CT scans after removing all descriptive information from the images. They tested negative or positive for COVID-19 and noted other features of CT of the lungs, including laterality, distribution pattern and lobe involvement. The laboratory results and clinical data were documented. Results: This study consisted of 90 COVID19 patients and 100 non-COVID-19 with ground glass opacities on CT chest. In terms of age; no statistically significant alteration was noted amid the 2 groups (p-value = 0.129). Non-COVID-19 cases with GGO; 6 patients have atypical bacterial pneumonia, 42 patients have GGO after viral pneumonia, 14 patients have interstitial pneumonia, 5 patients have PJP, eosinophilic pneumonia in 3 patients, 9 patients have hypersensitivity pneumonia, 6 patients have drug-induced lung injury, 5 patients have pulmonary alveolar hemorrhage and pulmonary edema in 11 patients (cardiogenic and noncardiogenic). Conclusion: Chest CT is rational for distinguishing ground glass opacities form COVID-19 and non-COVID-19 reasons, with less specificity for distinguishing COVID-19 from viral pneumonia and intermediate specificity for distinguishing COVID-19 from other reasons of ground glass opacities.